AB0415 High expression of gitr in serum and labial salivary glands from patients with primary sjögren's syndrome. (23rd January 2014) - Zhang, M.; Gan, X.; Feng, X.; Tan, W.; Lv, C.; Zhu, Y.; Gu, L.
Abstract : Objectives: Glucocorticoid-induced TNFR-related (GITR) is a gene coding for a member of the TNF receptor superfamily. After activated by its ligand GITRL, GITR could influence the activity of effector and regulatory T cells, participating in the development of several autoimmune and inflammatory diseases included rheumatoid arthritis and autoimmune thyroid disease. We previously reported that serum GITRL levels are increased in SLE patients compared with healthy controls (HC) [1 ]. Here, we tested the levels of GITR and GITRL in serum and labial salivary glands from patients with primary Sjögren's syndrome (SS), and investigated correlation of their expression levels with clinical and laboratory variables. Methods: Serum GITR and GITRL levels in 30 primary SS patients and 30 healthy controls were measured by ELISA. Patients were assessed for clinical and laboratory variables. GITR and GITRL levels in labial salivary glands were detected by immunohistochemistry. Results: Primary SS patients had significantly increased serum levels of soluble GITR and GITRL compared with controls [GITR:(5.65±3.43) ng/ml vs. (0.33±0.24) ng/ml, p<0.001; GITRL:(10.90±7.60)ng/ml vs. (0.36±0.28)ng/ml, p<0.001)]. Serum GITR and GITRL levels were positively correlated with IgG and ESR. More lymphocytes infiltration could be detected in SS patients compared to HC by Immunohistochemical analyses. Moreover, the expression levels of GITR in lymphocytic foci of the labial salivary glands from SS patients are higher than those in HC. However, GITRL expression was failed to be detected both in SS patient and HC. Conclusions: High serum GITR and GITRL levels in SS patients were associated disease activity variables included IgG and ESR, and the expression of GITR was increased along with more lymphocytes infiltration in labial salivary glands, suggesting an important role of GITR and GITRL in the pathogenesis of primary SS pathogenesis. References: Lei Gu, Lingxiao Xu, et al. Correlation of Circulating Glucocorticoid-Induced TNFR-Related Protein Ligand Levels with Disease Activity in Patients with Systemic Lupus Erythematosus. Clin. Dev. Immunol.2012, 2012:265868 Disclosure of Interest: None Declared